Does unemployment worsen babies’ health? A tale of siblings, maternal behaviour, and selection - De Cao, E; McCormick, B; Nicodemo, C (Elsevier, 2022)
We study in-utero exposure to economic fluctuations on birth outcomes by exploiting geographical variation in the unemployment rate across local areas in England, and by comparing siblings born to the same mother. Using rich individual data from hospital administrative records for 2003–2012, babies’ health is found to be strongly pro-cyclical. This overall result masks marked differences between babies born in the most affluent areas whose health at birth improves in a recession, and babies born in the average-to-lowest income deprived areas whose health deteriorates. Maternal alcohol consumption, smoking, and delay in the first antenatal care assessment - combined with parental income loss, are found to drive the results. While differences in maternal risky behaviours can explain the heterogenous effects.